2023
DOI: 10.1093/nc/niad002
|View full text |Cite
|
Sign up to set email alerts
|

Toward the unknown: consciousness and pain

Abstract: Studies of consciousness are hindered by the complexity of the brain, but it is possible to study the consciousness of a sensation, namely pain. Three systems are necessary to experience pain: the somatosensory system conveys information about an injury to the thalamus where an awareness of the injury but not the painfulness emerges. The thalamus distributes the information to the affective system, which modulates the intensity of the pain, and to the cognitive system that imparts attention to the pain. Imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It has to be pointed out that there are different aspects of consciousness including awareness of the environment by sensory stimuli, and volition, the voluntary control of thoughts and feelings (Albright et al , 2000). In understanding synaptic and molecular mechanisms of consciousness, it is highly possible that the very first component of consciousness can be tackled at the present time and consciousness of different forms of pain is a key indicator for consciousness (Ambron, 2023).…”
Section: Recent New Approaches For Studying Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be pointed out that there are different aspects of consciousness including awareness of the environment by sensory stimuli, and volition, the voluntary control of thoughts and feelings (Albright et al , 2000). In understanding synaptic and molecular mechanisms of consciousness, it is highly possible that the very first component of consciousness can be tackled at the present time and consciousness of different forms of pain is a key indicator for consciousness (Ambron, 2023).…”
Section: Recent New Approaches For Studying Consciousnessmentioning
confidence: 99%
“…Acute pain, which is a short-lasting stimulus, is known to increase the level of consciousness. It has been proposed that sensory pain-related consciousness may provide an excellent model for studying consciousness itself (Tiengo, 2003;Gu et al , 2013;Ambron, 2023). In patients with DOC, it has been reported that there is a strong correlation between the responsiveness to nociceptive stimuli and the level of consciousness (Thibaut et al , 2018).…”
Section: Pain and Consciousnessmentioning
confidence: 99%
“…It has to be pointed out that there are different aspects of consciousness including awareness of the environment by sensory stimuli, and volition, the voluntary control of thoughts and feelings (Albright et al, 2000). To understand synaptic and molecular mechanisms of consciousness, it is highly possible that the very first component of consciousness can be tackled at the present time and consciousness of different forms of pain is a key indicator for consciousness (Ambron, 2023).…”
Section: Key Thalamus‐cortical Networkmentioning
confidence: 99%
“…Acute pain, which is a short‐lasting stimulus, is known to increase the level of consciousness. It has been proposed that sensory pain‐related consciousness may provide an excellent model for studying consciousness itself (Ambron, 2023; Gu et al, 2013; Tiengo, 2003). In patients with DOC, it has been reported that there is a strong correlation between the responsiveness to nociceptive stimuli and the level of consciousness (Thibaut et al, 2018).…”
Section: Pain and Consciousnessmentioning
confidence: 99%
“…The management [9,10] However, many chronic pain studies have shown that dysfunction of cognitive control may have significant implications for the onset and maintenance of chronic pain [11,12]. The interaction between somatosensory, emotional, and cognitive systems produces the experience of pain [13]. Studies have also shown that cognitive or emotional factors are strongly correlated with resting-state fMRI data, suggesting that the brain retains some activity for these pain-related factors even at rest [14].…”
Section: Introductionmentioning
confidence: 99%